Comparing the efficacy of different antibiotic regimens on osteomyelitis: A network meta-analysis of animal studies - Shi, Xiangwen; Wu, Yipeng; Ni, Haonan; Chen, Xi; Xu, Yongqing (Frontiers in Medicine, 2022)
Background Despite the surge in the number of antibiotics used to treat preclinical osteomyelitis (OM), their efficacy remains inadequately assessed. Objective To establish network comparisons on the efficacy of antibiotic regimens on OM in animal studies. Methods PubMed, Embase, Web of Science, and The Cochrane Library were searched from inception to March 2022 for relevant articles. Odds ratios (ORs) were generated for dichotomous variants, and the standard mean difference (SMD) was calculated for constant variables. The predominant outcomes were the effective rate of sterility, also known as sterility rates, as well as the bacterial counts at the end of the experiments and antibiotic concentrations in serum or bone. All the network meta-analyses were performed using STATA MP 16.0. This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO; no. CRD42022316544). Results A total of 28 eligible studies with 1,488 animals were included for data analysis, including 13 antibiotic regimens. Regarding the effective rate of sterility, glycopeptides (GLY), linezolid (LIN), rifampicin (RIF)+β-Lactam, and β-Lactam showed significant efficacy compared with placebo (OR ranging from 0.01 to 0.08). For radiological grade, only RIF+GLY (SMD: −5.92, 95%CI: −11.65 to −0.19) showed significant efficacy compared with placebo. As for reducing bacteria count, fosfomycin (FOS), tigecycline (TIG), GLY, LIN, RIF, RIF+β-Lactam, RIF+GLY, aminoglycosides (AMI), and clindamycin (CLI) showed significant efficacy compared with placebo (SMD ranging from −6.32 to −2.62). Moreover, the bone concentrations of GLY were higher 1 h after administration and the higher blood concentrations were higher after 1 h and 4 h compared with the other antibiotics. Conclusion Multiple antibiotic regimens showed significant efficacy in animals with OM, including increasing effective rates of sterility, reducing bacterial counts, and lowering radiological scores. Among them, RIF+GLY was the most promising treatment regimen owing to its optimal efficacy. Based on the preclinical studies included in our meta-analysis, head-to-head clinical randomized controlled trials are required to confirm these findings in humans.